Turbulence in high growth and declining industries - Rui Baptista; Murat Karaöz (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
We examine turbulence over the product life cycle using the lowest possible level of industry aggregation, allowing for the use of panel data to study the evolution of single product markets. We find that replacement of exiting firms by subsequent entry plays a primary role in generating turbulence in high growth markets, while displacement of incumbents by recent entrants is the main selection force in declining markets. As product life cycles progress, trial-and-error entry subsides, and turbulence decreases.
Keywords: L11; 330; Entry; Exit; Selection; Product life cycle; Replacement; Displacement; Marktstruktur; Wettbewerb; Produktlebenszyklus; Markteintritt; Marktaustritt; Wachstumsbranche; Schrumpfungsbranche; Portugal